Hydrophobicity properties of graphite and reduced graphene oxide of the polysulfone (PSf) mixed matrix membrane - Akhair, S. H. M.; Harun, Z.; Basri, H.; Ahmad, R. A. R.; Rashid, A. Q. A.; Azhar, F. H. (Materials and Energy Research Center, 2018)
Hydrophobicity properties of graphite and reduced graphene oxide (rGO) (from exfoliated graphite/rGO) towards PSf polymer membrane characteristic and properties at different additives weight concentrations (1, 2, 3, 4 and 5 wt. %) were investigated. Both PSF/graphite and PSf/rGO membranes were characterized in term of hydrophobicity, surface bonding, surface roughness and porosity. FTIR peaks revealed that membrane with graphite and reduced graphene oxide nearly diminished their O-H bonding which was opposite to the graphene oxide peak that shows a strong O-H bonding as increased exfoliated times. These results were in line with the contact angle results that showed strong hydrophobicity of graphite and reduced graphene oxide membranes as increased these additives concentration. The effect of strong hydrophobicity in these membranes also has resulted in smoother surface roughness compared to pristine PSf membrane. Further investigation of the performance of water flux also proved that both above membranes have strong hydrophobic effect, with the lowest pure water flux rate (L/m2h) was given by PSf/rGO 3% membrane at 19.2437 L/m2h.